PARENTS’ PERCEPTION IN SELECTING TELEVISION PROGRAMS FOR MORAL DEVELOPMENT OF PRIMARY SCHOOL-AGED CHILDREN IN DUSUN SIMPANG PAWUO, DESA PULAU TERAP, KECAMATAN KUOK - Yona Hazlina; Gustimal Witri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This study aimed to determine the perception of parents in choosing television programs for the moral development of elementary school children in Kuok, Dusun Simpang Pawuo, Desa Pulai Terap RT 04 RW 02. This research utilized descriptive quantitative research. The subjects of this research were parents of elementary school students who lived at Dusun Simpang Pawuo RT 02 RW 04. The data were collected through observation, interviews, questionnaires, and documentation. Then, the data were analyzed by descriptive quantitative analysis techniques. The results indicated that the percentage of the questionnaire on each indicator was more than 70%. The percentage of the indicator for Opinion was 87.2%, Response was 83.51%, Meaning was 80.75%, and Perception was 77.49%. This implied that first, parents must provide directions and understandings to children about the programs to be watched and also must provide assistance and explanations. Second, parents must provide supervision to the children so that they will be careful in choosing television programs. Third, parents should guide children to watch the programs that educate and uphold moral values in order that children could minimize watching unuseful programs. Four, admonitions and punishments from parents would provide a deterrent effect when children watched the uneducated programs. It was expected that through these efforts parents could guide the children to watch the programs that improved the moral reasoning of primary school-aged children at Dusun Simpang Pawuo RT 04 RW 02, Desa Pulau Terap, Kecamatan Kuok.